Scope of Stem Cells in Periodontal Regeneration - Tom B.D.S, Tintu (Journal of Neonatal Surgery, 2025)
Periodontal disease (also called gum disease) is an infection that affects the tissues around tooth roots, and it is a very common oral health problem around the globe. This study looked into the possibilities of a stem cell therapy for periodontal regeneration, especially in their role of tissue repair and dental health advancement. It investigated the biological properties of mesenchymal stem cells (MSCs), dental pulp stem cells (DPSCs), and periodontal ligament stem cells (PDLSCs) as well as their regenerative potential. Finally, the application of scaffold-based approaches, as well as cell delivery systems, was reviewed with respect to whether the methodology has been commercialized. Major issues were also addressed- including ethical concerns, regulatory constraints, and the failure of a standard protocol for clinical integration. Future perspectives are directed at the improvement of treatment efficacy by means of personalized stem cell therapies and biomaterial innovations. This research contributed significantly to the field of regenerative dentistry and proposes the stem cells as a transformative means for the management of periodontal disease (which is also known as gum diseases).